The crude aqueous extract of Piper betle L. and its antibacterial effect towards Streptococcus mutans - Nalina, T.; Rahim, Z.H.A. (2007)
In this study, the antimicrobial influence of crude aqueous extract of Piper betle L. on Streptococcus mutons (S. mutans) was investigated. The focus of the antimicrobial effects includes the ultrastructure and acid producing properties of S. mutans. Transmission electron microscopy (TEM) was used to determine the effect of the extract on the ultrastructure of S. mutans. Analysis of the effect on the acid producing properties was analyzed by pH drop assay. The investigation was further carried out to determine the possible chemical components of the extract using thin layer chromatography (TLC), bioautography and gas chromatography mass spectrometry (GCMS). From the micrographs of the transmission electron, it was found that the crude extract of Piper betle L. leaves causes plasma cell membrane damage and coagulation of the nucleoid. The extract was found to significantly reduce acid producing properties of the bacteria. Chemical analysis of the extract showed that hydroxychavicol, fatty acids (stearic and palmitic) and hydroxy fatty acid esters (stearic, palmitic and myristic) as the main components. It was suggested from the results obtained that the crude extract of Piper betle L. leaves may exert anticariogenic activities that are related to decrease in acid production and changes to the ultrastructure of S. mutans. Further study will be carried out to determine if the effect observed is attributed to the presence of hydroxychavicol, fatty acids and hydroxy fatty acid esters in the extract.